Photodegradation of bisphenol a using wo3/zno photocatalyst under visible light irradiation - Mokhtar, Hamizah; Mohd Hir, Zul Adlan; Rafaie, Hartini Ahmad; Nik Ramli, Nik Fatin Nabihah Atiqah (Universiti Teknologi MARA (UiTM), 2023)
The issues on the safety and dwindling of water quality due to the presence of exogenous endocrine-disrupting chemicals (EDCs) such as Bisphenol A (BPA) have become a major toxicological threat and growing concern. In a bid to curb the pollutants accumulation in water, semiconductor-mediated photocatalysis has been shown to be better suited for the removal of such organic pollutants because the technique offers a green and sustainable process by utilizing natural solar light as the energy source to mitigate the pollutants. ZnO has formerly been used as a photocatalyst, but this material has a wide band gap of 3.37 eV that can only be fully employed under ultraviolet irradiation and accounts for less than 5% of solar radiation. Therefore, the doping of low band gap material such as WO3 into ZnO lattice could provide ideal surface characteristics enhancement for BPA degradation. The coupling could maximize the redox potential in which the flow of electrons from the conduction band of WO3 to ZnO is expected. In this study, WO3/ZnO composite photocatalyst was synthesized at various mol ratios via simple chemical precipitation method. The degradation of BPA in aqueous solution under visible light irradiation (23 W) over 0.5 g of WO3/ZnO (1:3) composite photocatalyst was shown to achieve the best degradation percentage of 65.73% within 180 min.